Teaching writing through the immigrant story - Ostman, Heather; Tinberg, Howard B., 1953-; Martínez, Danizete (Utah State University Press, 2021)
"Explores the intersection between immigration and pedagogy via the narrative. Embedded in the contexts both of student writing and student reading of literature, scholars engage the topic of immigration within writing and literature courses for extending, critiquing, and challenging assumptions about justice and equity, and deepening students' sense of ethics and humanity"--